2011
DOI: 10.3945/an.111.000398
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Chronic Lung Disease: A Review of Molecular Mechanisms and Clinical Studies

Abstract: Vitamin D is classically recognized for its role in calcium homeostasis and skeletal metabolism. Over the last few decades, vitamin D deficiency has increased in prevalence in adults and children. Potential extraskeletal effects of vitamin D have been under investigation for several diseases. Several cross-sectional studies have associated lower vitamin D status with decreased lung function. This finding has prompted investigators to examine the association of vitamin D deficiency with several chronic lung dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 96 publications
2
92
0
8
Order By: Relevance
“…In addition, some studies linked the actions of vitamin D to inhibited proliferation of metalloproteinases of the extracellular matrix (ECM) as well as the balance of type III collagen synthesis by fibroblasts (31). The ECM of lung tissue plays a key role in the structure and mechanical properties of the lungs, thus reflecting pulmonary function (5,32).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies linked the actions of vitamin D to inhibited proliferation of metalloproteinases of the extracellular matrix (ECM) as well as the balance of type III collagen synthesis by fibroblasts (31). The ECM of lung tissue plays a key role in the structure and mechanical properties of the lungs, thus reflecting pulmonary function (5,32).…”
Section: Discussionmentioning
confidence: 99%
“…Enfin, le déficit en vitamine D serait lié à des fonctions macrophagiques altérées (chimiotactisme et phagocytosealtérés, augmentation de production de cytokines proinflammatoires) [4,5,6,7,8]. Toutefois, ces constatations restent controversés, des études récentes n'ont pas trouvées de lien entre le statut en vitamine D et les marqueurs d'atopie, l'asthme et la dérmatite atopique aussi bien chez les enfants que chez les adultes [4,11,12,13].…”
Section: Materiels Et Methodes:-unclassified
“…Several studies across ethnic backgrounds have demonstrated a positive association between prevalence of tuberculosis and decreased concentrations of vitamin D [17] A meta-analysis of studies demonstrated that participants with tuberculosis had significantly lower serum 25(OH)D concentrations compared to matched controls [18]. Several cross-sectional studies have reported an association of vitamin D deficiency with decreased lung function [19].…”
Section: Vitamin D and The Immune Systemmentioning
confidence: 96%